DIGITAL REPRESENTATION OF WOMEN POLITICIANS IN INDONESIA: YOUTH PERSPECTIVES AND SELF-PORTRAYAL ON SOCIAL MEDIA - Kusumarani, Riri; Majid, Darmawati; Parlina, Anne; Nugroho, Ari Cahyo (JWP (Jurnal Wacana Politik), 2025)
Less than 25% of seats in Indonesia’s House of Representatives are held by women politicians. While studies have explored the topic of women in Indonesian politics, this article adopts a unique approach by examining the use of social media as a political marketing tool by women politicians in Indonesia during the 2024 pre-presidential election period. Key questions include how women politicians are portrayed on social media, how they portray themselves, and how Indonesian youths perceive them. Possible mismatches between portrayals are also considered. This study specifically analyzes and maps the characteristics of social media posts from 36 women politicians across their platforms. With the growing involvement of young people in the political arena, understanding younger generations’ views on women politicians is crucial for comprehending social media’s impact on Indonesia’s democratic system. The findings contribute to the understanding of young people’s interest in politics, particularly concerning women in politics, and offer insights into the potential influence of social media on future elections in Indonesia.